Correction: Self-reported impact of the COVID-19 pandemic, affective responding, and subjective well-being: A Swedish survey. - Maria Gröndal; Karl Ask; Timothy J Luke; Stefan Winblad (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0258778.].